Barriers to and facilitators of the identification, management and referral of childhood anxiety disorders in primary care: a survey of general practitioners in England - O’Brien, D; Harvey, K; Creswell, C (BMJ, 2019)
Objectives Although anxiety disorders are the most common emotional disorders in childhood and are associated with a broad range of negative outcomes, only a minority of affected children receive professional support. In the UK, general practitioners (GPs) are seen as ‘gate-keepers’ to mental health services. The aim of this study was to examine the extent to which GPs experience barriers to and facilitators of identifying, managing and accessing specialist services for these disorders, as well as factors associated with GPs’ confidence. Design and setting Cross-sectional, self-report questionnaire in primary care, addressing identification, management and access to specialist services for children (under 12 years) with anxiety disorders. Participants 971 GPs in England. Primary outcomes The primary outcomes for this research was the extent to which GPs felt confident (1) identifying and (2) managing anxiety disorders in children. Results Only 51% and 13% of GPs felt confident identifying and managing child anxiety disorders, respectively. A minority believed that their training in identification (21%) and management (10%) was adequate. Time restrictions inhibited identification and management, and long waiting times was a barrier to accessing specialist services. Being female (Ex(B)=1.4, 95% CI 1.1 to 1.9) and being in a less deprived practice (Ex(B)=1.1, 95% CI 1 to 1.1) was associated with higher confidence identifying childhood anxiety disorders. Being a parent of a child over the age of 5 (Ex(B)=2, 95% CI 1.1 to 3.5) and being in a less deprived practice (Ex(B)=1.1, 95% CI 1 to 1.2) was associated with higher confidence in management. Receipt of psychiatric or paediatric training was not significantly associated with GP confidence. Conclusions GPs believe they have a role in identifying and managing childhood anxiety disorders; however, their confidence appears to be related to their personal experience and the context in which they work, rather than their training, highlighting the need to strengthen GP training and facilitate access to resources and services to enable them to support children with these common but debilitating conditions.